cho $2.(x+y)=5.(y+z)=3.(z+x)$
Chứng minh rằng $\frac{x-y}{4} = \frac{y-z}{5}$
Đề đúng phải thế này
Từ $5.(y+z)=3.(z+x) => \frac{z+x}{5}=\frac{y+z}{3}=\frac{x+z-y-z}{2}=\frac{x-y}{2}$(Theo t/c của DTSBN)
$=> \frac{z+x}{5} = \frac{x-y}{2} <=> \frac{x+z}{10}=\frac{x-y}{4}$ (1)
Lại có: $2.(x+y)=3.(z+x) => \frac{x+y}{3}=\frac{z+x}{2}=\frac{x+y-x-z}{1}=y-z$ (Theo t/c của DTSBN)
$=> \frac{x+z}{2}=y-z <=> \frac{x+z}{10} = \frac{y-z}{5}$ (2)
Từ (1) (2) $=> \frac{x-y}{4} = \frac{y-z}{5}$ (đpcm)
Last edited by a moderator: